Modification of the existing maximum residue level for fluopyram in purslanes. (21st September 2017) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer CropScience submitted a request to the competent national authority in the Netherlands to modify the existing maximum residue level (MRL) for the active substance fluopyram in purslanes. The data submitted in support of the request were found to be sufficient to derive a MRL proposal for purslanes. Adequate analytical methods for enforcement are available to control the residues of fluopyram in plant matrices/on the commodity under consideration. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of fluopyram according to the reported agricultural practice is unlikely to present a risk to consumer health.